Galeni In Hippocratis Epidemiarum librum I commentariorum I-III versio Arabica : Edidit, in linguam Anglicam vertit, commentatus est - Vagelpohl, Uwe (2015)
This volume offers the first critical edition of Book I of the Arabic translation of Galen's Commentary on the Hippocratic Epidemics. The Arabic text is accompanied by an English translation and extensive notes on the differences between the Greek original and the Arabic version. The introduction outlines the complex history of the Greek and Arabic text and discusses the author, date and stylistic features of the Arabic translation.